THE CONDITION OF WATES GROUNDWATER BASIN FOR PRA TEMON INTERNATIONAL AIRPORT CONSTRUCTION KULONPROGRO DIY - Purwanto Purwanto; Arif Rianto Budi Nugroho; Intan Paramita Haty (Techno LPPM, 2015)
Underground water is a component in the hydrological cycle which takes place in nature,formed by rainwater that seeped into the soil in the recharge area and flew through the media layer ofrock acting as a carrier layer of water (aquifer) in ground water basin, where is under the groundleading to discharge area. Wates basin’s groundwater includes the Wates, Temon, Panjatan, Lendah,Brosot, a little part of the Sentolo and Pengasih District located in Unit Plateau of volcanics fluvio,beach units and sand dunes with the alluvial material consisting of sand, gravel, silt, and clay, flatmorphology, relative lithology and groundwater characteristics. This lithology is potential with theoccurrence of groundwater conservation system changes if there is an excessive ground waterextraction in the region which can be characterized by the increase in salinity in ground water.The main objective of this study is to fully assess the qualitative and quantitative groundwaterin the Wates Groundwater BasinBasin due to Temon International Airport construction in its relationto maintain the sustainability of groundwater systems.The methods in this study consists of several steps, starting from observation and rock’s / soildescription include: measurement of rock bedding, measurement of structural geology elements,observation of morphological conditions, and sampling soil / rock to be tested in laboratoryconcerning about the content of its mineralogy, texture and structure. The cross-section will showtheinformation of quantity / amount of groundwater that exist in the research area and the coastidentification towards the potential intrusion of sea water. The results of mineralogical analysis ofrocks and hydrochemical groundwater will provide information on the distribution of groundwaterquality. This conditions will certainly change the start of construction and post construction of theairport. Information about the mineralogical content of rocks, hydrochemical content of water andaquifer configuration will be able to contribute as an efforts in the groundwater area of InternationalAirport Temon, DIY.Keywords : groundwater, aquifer, electrolite conductivity,seawater intrusion